2002
DOI: 10.1159/000065542
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Genes from Nitrate-Tolerant Rat Aorta

Abstract: Organic nitrates act as vasodilators and have long been used for treatment of cardiovascular diseases. However, the therapeutic effect of nitrates is limited by induction of nitrate tolerance which is associated with endothelial dysfunction and enhanced vasoconstriction. Multiple mechanisms cause nitrate tolerance including alterations in gene expression. To identify genes whose expression is altered due to chronic treatment with nitroglycerin (NTG), nitrate-tolerant rats were made by infusion of NTG for 3 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 24 publications
2
3
0
1
Order By: Relevance
“…Overall, the gene array study revealed that NTG caused substantial and broad changes in the gene expression of a number of ECM proteases and adhesion molecules (Tables 2–4). The ability of NTG to cause extensive cellular gene regulation is consistent with our previous observation [26], confirmed by others [33], that wide-spread changes in vascular gene expression occurred in rats after chronic exposure and tolerance development, to NTG in vivo .…”
Section: Discussionsupporting
confidence: 92%
“…Overall, the gene array study revealed that NTG caused substantial and broad changes in the gene expression of a number of ECM proteases and adhesion molecules (Tables 2–4). The ability of NTG to cause extensive cellular gene regulation is consistent with our previous observation [26], confirmed by others [33], that wide-spread changes in vascular gene expression occurred in rats after chronic exposure and tolerance development, to NTG in vivo .…”
Section: Discussionsupporting
confidence: 92%
“…Our results confirmed previous observations that exposure to NTG may cause extensive changes in cellular and tissue gene regulation, as were shown for THP-1 macrophages [19], and in vascular tissues [48; 49]. However, the specific genes that were affected in the present experiment differed substantially from those observed after acute high-concentration exposure [19].…”
Section: Discussionsupporting
confidence: 92%
“…At the top of the list are α 2 - and β-globins, which have been observed to be upregulated in rat aorta chronically treated with nitroglycerin. 22 One of the most commonly recognized features of atherosclerosis in diabetics is an upregulation of CD36 messenger ribonucleic acid (mRNA) and protein. This response by macrophages to hyperglycemia contributes to accelerated atherogenesis in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%